2006
DOI: 10.1111/j.1600-051x.2006.01028.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal treatment needs of diabetic adults

Abstract: The poor periodontal status of our diabetic patients indicates a need to establish a comprehensive oral health promotion programme for diabetics based on collaboration between dental and general health care professionals involved in diabetic care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…[11] It has been observed that patients with uncontrolled diabetes have an increased risk for periodontal diseases. One of the studies has also shown a two-way relationship between periodontal disease and diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…[11] It has been observed that patients with uncontrolled diabetes have an increased risk for periodontal diseases. One of the studies has also shown a two-way relationship between periodontal disease and diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…Suboptimal oral hygiene is among the most common risk factors for aspiration pneumonia; resolving the problem of oral hygiene could have prevented 21% of all aspiration pneumonia cases in one NH sample (Quagliarello et al, 2005). Other systemic diseases associated with inadequate oral hygiene and resulting poor oral health are diabetes (Bakhshandeh, Murtomaa, Mofid, Vehkalahti, & Suomalainen, 2007; Promsudthi et al, 2005) and coronary artery disease (Desvarieux et al, 2003; Desvarieux et al, 2005; Kurihara et al, 2007). Deficient oral health negatively affects quality of life and mortality as well (Padilha, Hilgert, Hugo, Bós, & Ferrucci, 2008).…”
Section: Relationship Between Care-resistant Behavior and Oral Healthmentioning
confidence: 99%
“…Inflammation of the gingival tissues, either with or without periodontal disease, has been related to adverse outcomes in pregnancy, such as premature-birth and low-birth-weight infants [7]. Other systemic diseases associated with inadequate oral hygiene and resulting poor oral health include diabetes [810] and coronary artery disease [11]. Inadequate oral health negatively impacts quality of life and mortality, as well [12].…”
Section: Introductionmentioning
confidence: 99%